Epsipo Strategy: Character Strengthening through Cultural Project-Based Mathematics Learning - Dinata, Karsoni Berta; Rosidin, Undang; Suprapto, Irawan; Sutiarso, Sugeng; Dwi Yulianti; Sumarno (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
Mathematics learning must be oriented towards achieving mathematical skills and shaping students' character. The nature of mathematics as the highest form of rationality, often results in the teacher's view that mathematics is only intended for cognitive development, but it is difficult to develop students' character. For this reason, the purpose of this research is to develop mathematics learning to improve students' cognitive abilities and character. This study uses an integrative literature review method by integrating ethnomathematical theory and project-based learning to build a theoretical framework for the Epsipo Learning Strategy (Ethnomathematics-Project-based Learning). The epsipo strategy is basically an effort that can be made to teach mathematics through a project with a cultural context. The project-based learning model has contributed to realizing meaningful mathematics learning, but it lacks value instillation. The ethnomathematics initiated by D'Ambrosio is rich in moral and social values. The two theories complement each other with their own advantages. Through the implementation of the Epsipo strategy, it is hoped that students will have the knowledge and ability to think mathematically and develop their character. It is hoped that through this strategy, mathematics learning is not only oriented towards achieving cognitive aspects but also to strengthen students' character.